2018
DOI: 10.1002/ajmg.a.38722
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in EBF2 was segregated with imperforate anus in a family across three generations

Abstract: The etiology of imperforate anus, a major phenotype of anorectal malformation (ARM), is still unknown and not a single gene has been reported to be associated with it. We studied a Korean family with six affected members with imperforate anus across three generations by whole exome sequencing and identified a missense mutation in the EBF2 gene (c.215C > T; p.Ala72Val). This mutation is completely segregated with the disease phenotype in the family and is evolutionarily highly conserved among diverse vertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Three genes have been identified that cause syndromic forms of ARA when mutated: SALL1 in Townes–Brocks syndrome (Kohlhase, Wischermann, Reichenbach, Froster, & Engel, ), HLXB9 in Currarino syndrome (Belloni et al, ), and GLI3 in Pallister–Hall syndrome (Böse, Grotewold, & Ruther, ). Kim et al () reported that a missense mutation in EBF2 was segregated with imperforate anus in a family across three generations. EBF proteins interact with important regulators of development, including Hedgehog and BMP signaling (El‐Magd, Allen, McGonnell, Otto, & Patel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Three genes have been identified that cause syndromic forms of ARA when mutated: SALL1 in Townes–Brocks syndrome (Kohlhase, Wischermann, Reichenbach, Froster, & Engel, ), HLXB9 in Currarino syndrome (Belloni et al, ), and GLI3 in Pallister–Hall syndrome (Böse, Grotewold, & Ruther, ). Kim et al () reported that a missense mutation in EBF2 was segregated with imperforate anus in a family across three generations. EBF proteins interact with important regulators of development, including Hedgehog and BMP signaling (El‐Magd, Allen, McGonnell, Otto, & Patel, ).…”
Section: Discussionmentioning
confidence: 99%